ЕЛИМИЗДЕ МАКРОЭКОНОМИКАЛЫҚ ТУРАҚЛЫЛЫҚТЫ ТӘМИЙИНЛЕУ - Хожалепесов, П. (FAN va JAMIYAT, 2017)
The article deals with the stages of development of small business and private entrepreneurship. The author of the article analyzes the importance of domestic and foreign investments in the country and the potential of industrial enterprises in the country. The development of competitor capable goods to industrial enterprises and the study of the socio-economic development of Karakalpakstan were also presented in the article.